Analisis Kompetensi dan Kesiapan Mahasiswa PGSD dalam Pengelolaan Pembelajaran ABK di Sekolah Inklusi - Endang Poerwanti; Nawang Sulistyani (Universitas Negeri Malang, 2021)
One of the superior profiles that prospective elementary school teacher students should have is competence in providing inclusive education services. The importance of these competencies is analyzed in this study to describe the competence and readiness of University Muhammadiyah Malang Elementary School Teacher Education Study Program students in managing ABK learning in inclusive schools. The mixed-method research with research subjects was 300 students, five lecturers, and one East Java inclusion development team. The research data were collected through a group discussion forum, questionnaires, and documentation which were analyzed using descriptive qualitative and quantitative techniques. From the research results obtained the formulation of ten competencies in the management of inclusive learning that should be mastered by prospective elementary school teacher students. The results also showed that the majority of UMM PGSD Study Program students had good readiness in mastering the ten competencies, including 85 percent mastering criteria 1, 2, 3, 4, 7, and 8; 65 percent mastered criteria 5 and 6; 80 percent mastered criteria 9 and 10. Salah satu profil unggul yang hendaknya dimiliki mahasiswa calon guru SD adalah kompetensi dalam memberikan layanan pendidikan inklusi. Pentingnya kompetensi tersebut dianalisis dalam penelitian ini dengan tujuan untuk mendeskripsikan kompetensi dan kesiapan mahasiswa Prodi PGSD Universitas Muhammadiyah Malang dalam pengelolaan pembelajaran ABK di sekolah inklusi. Penelitian ini menggunakan mix method dengan subjek penelitian adalah 300 mahasiswa, lima dosen dan satu tim pengembang inklusi Jawa Timur. Data penelitian dikumpulkan melalui forum group discussion, angket dan dokumentasi yang dianalisis dengan teknik deskriptif kualitatif dan kuantitatif. Dari hasil penelitian diperoleh rumusan sepuluh kompetensi pengelolaan pembelajaran inklusi yang hendaknya dapat dikuasai mahasiswa calon guru SD. Hasil penelitian juga menunjukkan bahwa mayoritas mahasiswa Prodi PGSD UMM memiliki kesiapan yang baik dalam menguasai sepuluh kompetensi tersebut, antara lain 85 persen menguasai kriteria 1, 2, 3, 4, 7 dan 8; 65 persen menguasai kriteria 5 dan 6; 80 persen menguasai kriteria 9 dan 10.